THE NEEDS ANALYSIS OF ELEMENTARY SCHOOL TEACHERS FOR MERDEKA CURRICULUM-BASED E MODULE ON NATURAL AND SOCIAL SCIENCES - Erna Risfaula Kusumawati (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2024)
The purpose of this study is to analyze the level of teachers' needs on a Merdeka Curriculum-based E module for Natural and Social Sciences. The subjects were 36 elementary school teachers from 6 districts. The research instrument used was a questionnaire. The results of the study showed that the average value of the Merdeka Curriculum teaching module of Natural and Social Sciences requirement was 3.64 (much needed); (2) the average need for Merdeka Curriculum teaching e-modules is 3.61 (very much needed); (3) the average need for teaching module development is 3.78 (very much needed); (4) the average need for literacy-based and differentiated science teaching modules is 3.7 (much needed); (5) the average need for an interesting, contextual, and pictures-based Natural and Social Sciences teaching module is 3.76 and (6) the average need for Natural and Social Sciences teaching module which contains a HOTS-based assessment is 3.58 (very much needed). The description of the needs analysis shows that elementary school teachers need (1) The Development of teaching modules in both digital and non-digital forms, one of which is in the Natural and Social Sciences subject (2) Natural and Social Sciences teaching modules that have attractive, contextual criteria, are equipped with pictures, and also contain an assessment component which is based on HOTS (3) The teaching module is also literacy-based and differentiated. This research implies that the result of the needs analysis can be used as a basis for the development of the Merdeka Curriculum-Based E Module on Natural and Social Sciences